2011
DOI: 10.21829/azm.2011.271741
|View full text |Cite
|
Sign up to set email alerts
|

Adiciones y aportaciones para el género Enoclerus gahan (Coleoptera: Cleridae) en bosques de clima templado en México

Abstract: Por medio del uso de trampas multiembudo tipo Lindgren cebadas con frontalina y otros atrayentes, colocadas en 12 localidades de bosque de clima templado en México, se obtuvieron seis especies del género Enoclerus (Coleoptera: Cleridae: Clerinae). Se llevó a cabo la diagnosis general y la clave de identificación de las especies capturadas para lograr su reconocimiento y caracterización. Éstegénero tiene un papel de gran importancia como depredador natural de escarabajos descortezadores y barrenadores. Se prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 25 publications
0
2
0
6
Order By: Relevance
“…Distribución. EUA, México (Estado de México, Distrito Federal, Durango, Guanajuato, Jalisco, Zacatecas) Barr y Foster, 1979;Schaeffer, 1921) Barr y Foster, 1979;Rifkind, 2022b;Schaeffer, 1921) (Barr, 1978a;Burke et al, 2011;Rifkind, 1997Rifkind, , 2022b Rifkind, 1997Rifkind, , 2022bToledo et al 2015) Rifkind, 1997;Toledo et al, 2015;Wolcott, 1947) (Rifkind, 1997). Material revisado.…”
Section: Aulicus Monticola Gorham 1882unclassified
See 3 more Smart Citations
“…Distribución. EUA, México (Estado de México, Distrito Federal, Durango, Guanajuato, Jalisco, Zacatecas) Barr y Foster, 1979;Schaeffer, 1921) Barr y Foster, 1979;Rifkind, 2022b;Schaeffer, 1921) (Barr, 1978a;Burke et al, 2011;Rifkind, 1997Rifkind, , 2022b Rifkind, 1997Rifkind, , 2022bToledo et al 2015) Rifkind, 1997;Toledo et al, 2015;Wolcott, 1947) (Rifkind, 1997). Material revisado.…”
Section: Aulicus Monticola Gorham 1882unclassified
“…Enoclerus decussatus (Klug, 1842) Distribución. EUA, México (Chihuahua, Durango, Estado de México, Guanajuato, Guerrero, Jalisco, Michoacán, Morelos, Oaxaca, Puebla, Veracruz) (Rifkind, 1997(Rifkind, , 2022b (Burke et al, 2011;Rifkind, 1997)…”
Section: Enoclerus Crinitus Rifkind 2012unclassified
See 2 more Smart Citations
“…Some examples of the predatory preferences of Cymatodera are the following: Cymatodera bicolor (Say) has been observed to prey on Chyptophorus verrucosus (Olivier) (Coleoptera: Cerambycidae) feeding on Cornus florida Linnaeus (Cornaceae) (Opitz 2010); a number of Cymatodera species are known to prey on economically important insect pests, such as Amyelois transitella Walker (Lepidoptera: Pyralidae) in Juglans regia Linnaeus (Juglandaceae) (Michelbacher and Davis 1961), and the parasitoids of galls of Disholcaspis mamma Kinsey (Hymenoptera: Cynipidae) found on several species of Quercus Linnaeus (Fagaceae) (Balduf 1926). Burke et al (2011) identified a number of Cymatodera species attracted to bark beetle aggregation pheromones and/or other volatiles emitted by the host tree in forest stands of central and southern Mexico affected by Dendroctonus Erichson and Ips De Geer (Coleoptera: Curculionidae: Scolytinae).…”
Section: Introductionmentioning
confidence: 99%